Effect of medium-chain triglycerides supplements and walking on health-related quality of life in sedentary, healthy middle-aged, and older adults with low BMIs: a randomized, double-blind, placebo-controlled, parallel-group trial - Ishikawa, Haruna; Kojima, Keiichi; Watanabe, Shinji; Nosaka, Naohisa; Mutoh, Tatsushi (Frontiers in Nutrition, 2023)
To extend individuals' healthy life expectancies, the improvement of subjective health and quality of life (QOL) has been increasingly prioritized, alongside the improvement of their physical functioning. Reports have indicated that intake of medium-chain triglycerides (MCTs) benefits the physical health of older individuals requiring nursing care, and athletes, and healthy individuals. But there are few studies investigating the effects of MCTs on subjective health and QOL. The present study sought to evaluate the combined effects of 12-week MCTs supplements and moderate-intensity walking exercise on the subjective health and QOL of middle-aged and older adults aged 60-74 with low BMIs (< 24 kg/m 2 ) and who had no exercise habits.Methods: A placebo-controlled, double-blind, parallel-group trial was conducted. Three MCTs supplement groups with different doses and fatty acid compositions were compared with a control group. The study used the SF-36v2 questionnaire to assess subjective health and health-related QOL (HRQOL).The result showed significant improvements in the scores on subscales of the physical QOL, such as Physical functioning and General health, and summary scores on the mental QOL, compared to the control.It is estimated that the combination of continuous intake of MCTs and walking exercise may affect HRQOL and improve subjective physical and mental health in sedentary, healthy, middleaged and older adults. 2 This is a provisional file, not the final typeset article Clinical Trial Registration: [https://rctportal.niph.go.jp/s/detail/um?trial_id=UMIN000046861], identifier [UMIN000046861].